Undocumented workers during Malaysia’s Movement Control Order (MCO) - Diana Peters; Marja Azlima Omar; Ramli Dollah; Wan Shawaluddin Wan Hassan (Transnational Press London, 2022)
Malaysia has a significant population of migrant labour force. Out of the 5.5 million migrant workers in the country, more than half are reported to be undocumented, with the state of Sabah being home to the highest population of undocumented migrant workers majority from the Philippines and Indonesia. Since the 1970s the scale of migration increased drastically with the arrival of large number of Muslim refugees from the war-torn southern Philippines, and economic migrants from rural areas of Indonesia, in hopes of achieving better economic and food security. This steady flow of foreign labour also coincided with the state’s economic development plan which saw labour intensive sectors such as constructions, plantation and timber boom. However, when the Covid-19 pandemic began to spread in Malaysia, job opportunities drastically reduced as the government pulled the brakes on almost all economic sectors and closed off the borders. The Movement Controlled Order (MCO) announced nationwide beginning 18 March 2020 thus increased the vulnerability of the undocumented irregular migrants, as the economic threat in the form of loss of wages and movement restrictions decreased the food security of this group.